2005
DOI: 10.1088/0963-0252/15/1/002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of diffuse barrier discharges in neon and helium

Abstract: Diffuse dielectric barrier discharges in neon and helium at atmospheric pressure were studied. The discharges were generated between two metal electrodes, both covered by an alumina layer and driven by ac voltage of frequency 10 kHz. The discharge gap was 2.2 mm and 5 mm, respectively. The discharges were investigated by electrical measurements and by temporally and spatially resolved optical emission spectroscopy. The experimental results revealed similar discharge behaviour in both gases being considered. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 21 publications
8
57
0
1
Order By: Relevance
“…It was well accepted that neon metastables and excimers have enough energy to ionize impurity nitrogen by Penning effect as shown in equations (5) and (6) [7] . for the breakdown.…”
Section: Breakdown Voltagementioning
confidence: 99%
See 1 more Smart Citation
“…It was well accepted that neon metastables and excimers have enough energy to ionize impurity nitrogen by Penning effect as shown in equations (5) and (6) [7] . for the breakdown.…”
Section: Breakdown Voltagementioning
confidence: 99%
“…Extensive work was done and the mechanism of diffuse barrier discharges in helium and nitrogen is now fairly well established [2][3][4][5] . It was reported that diffuse DBD can also be generated in atmospheric neon [6][7][8] , but more detailed investigations on neon DBD are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric barrier discharges (DBDs) are non‐equilibrium low‐temperature discharges. DBDs are operated in wide range of pressures1, 2 in different gases3–5 and therefore they are attractive for diversified industrial applications. These low‐temperature discharges, when operated at atmospheric pressure, are suitable for the treatment of materials which are sensitive to temperature and pressure, like thermolabile materials and biological substrates 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…42,43 The presence of uniform plasma characterised by lack of filaments 44 can be observed in Figure 5(b).…”
Section: Resultsmentioning
confidence: 95%